DEVELOPMENT OF AUTOMATED EXCITATION AUXILIARY CUTTING SIMILAR EXPERIMENT PROTOTYPE AND ITS MECHANICAL EXPERIMENT - LU JinNan; YUE JianGuang; XIE Miao; WANG PengFei (Jixie qiangdu)
Considering the current heavy mining and light digging in coal mines, limitations of the structural design of the fully mechanized excavation equipment, backward tunneling technology and other problems lead to inefficient tunneling. mining ratio is out of balance, at the same time, the comprehensive excavation equipment of the coal mine underground roadway is huge, the downhole environment is complicated, and the equipment is difficult to disassemble and assemble. It is difficult to analyze the mechanical properties of key components and cut efficiency improvement experiments under laboratory conditions. A method of active excitation assisted cutting is researched, this method is based on similarity theory, a similar model test bench with a ratio of 1:3 is established, modal experiments were performed firstly, the natural frequencies of the first six orders and the modal shapes of each order are obtained, the feasibility of the active vibration-assisted cutting experimental bench is verified, perform cutting experiments on the test bench separately with or without active excitation. With or without active excitation, the cutting contact force and cutting current change of the pick are measured. The experimental results show that during the same time period, when there is active excitation, the initial time for increasing contact force is 0.07 s earlier than when there is no excitation, longer duration, contact force is reduced by 0.12 kN compared with no excitation, after excitation, the average cutting current decreased by 1.12 A.Through the test bench based on Similarity theory, the active excitation vibration experiment and test can be carried out on the cutting arm of the road-header under limited laboratory conditions. Which provides a theoretical reference for selecting the best excitation-assisted cutting parameters. At the same time, it has opened up new ideas and new methods for the energy-saving and efficient work of the cutting machine cutting mechanism from the perspective of external excitation.